PENGARUH METODE PEMBELAJARAN DAN GAYA BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI - Ruknan, Ruknan (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The objective of this study is to determine the influence of learning methods and learning styles on the learning outcomes of economic subjects. The target population of this study are students of State Senior High School 5 Tangerang, and as an affordable population are students of Class X. Research sample is determined by cluster random sampling obtained by two classes that is experiment class and control class with each class there are 11 samples so that the number of analysis sample amounted to 44 students. The instrument used as a data collection tool is a questionnaire to categorize the learning style of the student into an independent learning style and dependent learning style. The test instrument of the learning result of economic subjects is multiple choice tests with valid number of 27 items and reliability coefficient of 0.91. The results were analyzed by Two-way Variance Analysis Technique. The conclusion of the research are: 1) there is influence of learning method to the learning result of economic subject, 2) there is influence of learning style method to the learning result of economic subjects, 3) there is interaction influence of learning method and learning style to the learning result of economic subjects, 4) There is influence of learning method to the learning result of economics subject to independent learning style. The result of learning of economic subjects in self-learning style which get problem solving learning method is higher than the method of recitation learning, and 5) there is no effect of learning method on the learning result of economic subjects on dependent learning style.